2014
DOI: 10.1136/bmjopen-2014-005947
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-related hospitalisations of trauma patients in Southern Taiwan: a cross-sectional study based on a trauma registry system

Abstract: ObjectivesTo provide an overview of the demographic characteristics of patients with positive blood alcohol concentration (BAC) and to investigate the performance of brain CT scans in these patients.DesignCross-sectional study.SettingTaiwan.Participants2192 patients who had undergone a test for blood alcohol of 13 233 patients registered in the Trauma Registry System between 1 January 2009 and 31 December 2012. A BAC level of 50 mg/dL was defined as the cut-off value. Detailed information was retrieved from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Moreover, because of different riding speeds, the impact energy may differ between collisions involving motorcyclists and those involving bicyclists. There is scarce information on the protective effect of helmet use in Taiwan, where motorcycle and bicycle accidents occur on relatively crowded streets [ 19 ]. Therefore, in this study we aimed to investigate the protective effect of helmet use during motorcycle and bicycle accidents by using a propensity score–matched study based on trauma registry system data over a seven-year period.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because of different riding speeds, the impact energy may differ between collisions involving motorcyclists and those involving bicyclists. There is scarce information on the protective effect of helmet use in Taiwan, where motorcycle and bicycle accidents occur on relatively crowded streets [ 19 ]. Therefore, in this study we aimed to investigate the protective effect of helmet use during motorcycle and bicycle accidents by using a propensity score–matched study based on trauma registry system data over a seven-year period.…”
Section: Introductionmentioning
confidence: 99%
“…21 In alcohol-intoxicated patients with less-severe injuries, brain CT was overused, with a higher proportion of negative findings for intracranial haemorrhage. 22 In an analysis of the sample of ED patient visits, representing ∼13 million ED visits nationwide, BAC-positive patients underwent more diagnostic tests and had longer ED stays. 28 Previous studies have reported alcohol use to be associated with higher hospital mortality and expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in ndings between this study and others that examine the effect of alcohol on injury severity may result from local variations among study populations and the utilization of our tertiary care center versus community hospitals. Relevant studies looked at diverse demographic and geographic communities, from our own study in the suburbs of New York City, to LA county 5 and even Taiwan 7,22 . Meta-analysis of these studies should be performed to normalize the demographic and geographical differences to more accurately determine alcohol's effect on injury.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the effects of alcohol on injury type and severity, but results have varied between study cohorts. [4][5][6][7] Some studies suggest that intoxicated patients have worse injuries. For example, one group found that pedestrians who had consumed alcohol were more injured (as determined by their Injury Severity Score (ISS)) and had longer hospital length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%